Efektivitas Pembelajaran Daring Mapel PJOK Pada Masa Covid-19 di SD Negeri 2 Bumisari (Universitas Negeri Semarang, 2022)
Problems that arise with online learning are the limitations of an unstable internet network, especially in villages, limited mastery of technology, and the lack of attention and support from parents for their children. The purpose of this study is to determine the level of effectiveness of PJOK online learning according to the views of students and teachers' views. This study uses a quantitative research design with a survey research model. The population in this study were all students in grades 4.5 and 6 at SD N 2 Bumisari with the sampling technique used using total sampling. Data collection techniques using (1) Observation (2) Questionnaire (3) Documentation. The data analysis technique used is descriptive analysis. The results of the study on the Effectiveness of Online Learning in PJOK at SD N 2 Bumisari Purbalingga according to the views of students, the results were very effective at 0%, the effective category was 87.5%, the less effective category was 12.5%, the ineffective category was 0%. Meanwhile, according to the teacher's view, the results obtained in the very effective category of 0%, the effective category of 100%, the less effective category of 0%, and the ineffective category of 0%. So it can be concluded that the effectiveness of maple PJOK's online learning in the school is in the effective category